Edukasi Aktivitas Fisik Terhadap Peningkatan Kualitas Hidup Lansia di Puskesmas Andalas Padang - Weni Mailita; Helmanis Suci (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
The elderly represent a vulnerable age group that often experiences a decline in physical, psychological, and social functions, ultimately affecting their quality of life. In the working area of Andalas Public Health Center in Padang, low participation in physical activities among the elderly is still evident due to limited knowledge and motivation. This community service program aimed to improve the quality of life of the elderly through physical activity education tailored to their abilities. Activities included interactive health education sessions, elderly exercise training, and the distribution of physical activity guidebooks. The participants consisted of 20 elderly individuals. Instruments used in this program included observation sheets to assess participation, the WHOQOL-BREF questionnaire to measure quality of life before and after the intervention, and a participant satisfaction evaluation form. The evaluation method involved a pre-test and post-test approach along with a focus group discussion (FGD) to explore perceptions and the impact of the education provided. The results showed an increase in elderly knowledge about the benefits of physical activity and improved quality of life scores, particularly in physical and psychological domains. Physical activity education has proven to be an effective promotive and preventive intervention in supporting elderly health at the community level.